No teens, no tech : how shortages of young workers hinder firm technology investments - Lipowski, Cäcilia [Verfasser] (My University, 2024)
„Firms in developed countries face increasing shortages of young workers. This paper studies the importance of young workers, particularly vocational trainees, for firm technology investments. Leveraging exogenous variation in trainee supply caused by an education reform in Germany in 2001, I show that a reduction in trainee supply decreases firm technology investments. This suggests complementarity between young workers and new technologies. Consistent with firms’ lower opportunity costs and higher returns to training young workers than incumbents, the effect is driven by firms exposed to new tech skills. These findings dampen hopes of counteracting labor shortages by substituting labor with capital.“ (author’s abstract; BIBB-Doku)

„Unternehmen in Industrieländern erleben einen zunehmenden Mangel an jungen Arbeitskräften. Die Autorin vom ifo Zentrum für Bildungsökonomik untersucht die Bedeutung junger Arbeitskräfte, insbesondere Auszubildender, für Unternehmensinvestitionen in neue Technologien. Sie zeigt anhand einer deutschen Bildungsreform im Jahr 2001, dass eine geringere Auszubildendenanzahl die Technologieinvestitionen der Unternehmen mindert. Dies lässt auf eine Komplementarität zwischen jungen Arbeitnehmenden und neuen Technologien schließen. Der Effekt wird durch Unternehmen verursacht, die einem raschen Qualifikationswandel ausgesetzt sind, sodass Auszubildende benötigt werden, um mit den neuesten Fähigkeiten ausgestattet zu sein.“ (Hrsg.; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; P 2.3 Auszubildende; G 2.3.4 Qualifikationswandel; 370; 330; Betrieb; Investitionen; Investitionspolitik; Technischer Wandel; Einflussfaktor; Junger Erwachsener; Auszubildender; Qualifikationswandel